2023
DOI: 10.3390/rs15051295
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Index (AQI) Did Not Improve during the COVID-19 Lockdown in Shanghai, China, in 2022, Based on Ground and TROPOMI Observations

Abstract: The lockdowns from the coronavirus disease of 2019 (COVID-19) have led to a reduction in anthropogenic activities and have hence reduced primary air pollutant emissions, which were reported to have helped air quality improvements. However, air quality expressed by the air quality index (AQI) did not improve in Shanghai, China, during the COVID-19 outbreak in the spring of 2022. To better understand the reason, we investigated the variations of nitrogen dioxide (NO2), ozone (O3), PM2.5 (particular matter with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Our study offers a fresh perspective on assessing the socioeconomic effects of the COVID‐19 pandemic by demonstrating how nighttime light remote sensing can efficiently track changes in urban socioeconomic activities resulting from public health prevention and control measures. Consistent with the findings of many other researchers (Ma et al., 2023; Xue et al., 2022; Yang et al., 2021), our research indicates that pandemic control measures implemented in Zhengzhou from September to October 2022 significantly dampened economic activity. Our study stands as a valuable resource for China and other regions as they evaluate the effectiveness of pandemic prevention and control methods.…”
Section: Discussionsupporting
confidence: 92%
“…Our study offers a fresh perspective on assessing the socioeconomic effects of the COVID‐19 pandemic by demonstrating how nighttime light remote sensing can efficiently track changes in urban socioeconomic activities resulting from public health prevention and control measures. Consistent with the findings of many other researchers (Ma et al., 2023; Xue et al., 2022; Yang et al., 2021), our research indicates that pandemic control measures implemented in Zhengzhou from September to October 2022 significantly dampened economic activity. Our study stands as a valuable resource for China and other regions as they evaluate the effectiveness of pandemic prevention and control methods.…”
Section: Discussionsupporting
confidence: 92%
“…Among these five air pollutants, NO 2 , which is primarily emitted by vehicle activities, decreased significantly, with a maximum decrease of 48.6% (Figure 2), which was consistent with previous studies in Jinan (54%; K. Li et al, 2022), Shanghai (50%; Q. Ma et al, 2023), the Beijing-Tianjin-Hebei region (65%; Ren et al, 2023), India (51%; Sekar et al, 2023), and Sri Lanka (82%; Pushpawela et al, 2023), etc. The most significant decrease in NO 2 was strongly associated with substantial restrictions on local traffic (Li & Lasenby, 2023;Llaguno-Munitxa & Bou-Zeid, 2023;Sekar et al, 2023;.…”
Section: Temporal Changes In Air Pollutant Concentrations In Differen...supporting
confidence: 90%
“…However, several studies have found that the lockdown measures do not significantly prevent air pollution (Le et al, 2020;P. Wang et al, 2020a;Mo et al, 2021;Song et al, 2021;Luo et al, 2022;Q. Ma et al, 2023;L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human premature death from respiratory and cardiovascular disorders is closely correlated with both fine particulate matter (PM2.5) and particulate matter (PM10) [29]. According to a number of studies, tiny particulate matter (PM2.5) poses a greater risk than fine particulate matter (PM10).…”
Section: Introductionmentioning
confidence: 99%